Barriers in online education for displaced universities: Insights from faculty and students - Iryna Glazkova; Natalia Falko; Olena Khomenko; Svitlana Khatuntseva; Nataliya Rula; Anzhelika Shulzhenko; Volodymyr Tatarin (Problems and Perspectives in Management)
The relevance of this study lies in the growing shift to online education for displaced universities due to war-related disruptions. The aim is to identify barriers faculty and students face in such institutions and propose strategies for creating a barrier-free educational environment. The study employs a survey-based method, analyzing responses from 224 students and 71 faculty members of a displaced Ukrainian university.Results highlight significant economic barriers, with 79% of students reporting financial difficulties affecting access to stable Internet, modern devices, and essential resources. Virtual isolation was noted by 79% of students as a challenge in maintaining social connections, while 78% cited reduced motivation characterized by the dominance of avoidance motives. Faculty reported psychological stress (85.6%), including anxiety (75%), tremors (54%), and sleep disturbances (45%). Organizational barriers, such as adapting practical courses to online formats and increased workloads due to asynchronous learning, were also prominent.These findings underscore the need for targeted strategies to address the barriers and promote inclusivity and effectiveness in online education. A comprehensive approach integrating institutional, pedagogical, and policy-level interventions is critical for overcoming these challenges.